The Global Political Economy of Communication
XV, 193 p.
Keywords: This collection examines the theoretical, analytical and political implications of global developments involving telecommunications and related technologies. The book's contributors - from fields such as economics, political science and communication studies - relate research on the political economy of communication with the work of international political economy scholars. The book stimulates cross-disciplinary debates among readers in these and other areas in order to, first, critically evaluate recent global developments involving communications and, second, to encourage the development of a more holistic and inclusive approach to these and related issues.